Spastin mutations are frequent in sporadic spastic paraparesis and their spectrum is different from that observed in familial cases. Issue 3 (31st July 2005) - Depienne, C; Tallaksen, C; Lephay, J Y; Bricka, B; Poea-Guyon, S; Fontaine, B; Labauge, P; Brice, A; Durr, A
Abstract : Background: SPG4 encodes spastin, a member of the AAA protein family, and is the major gene responsible for autosomal dominant spastic paraplegia. It accounts for 10–40% of families with pure (or eventually complicated) hereditary spastic paraparesis (HSP). Objective: To assess the frequency of SPG4 mutation in patients with spastic paraplegia but without family histories. Methods: 146 mostly European probands with progressive spastic paraplegia were studied (103 with pure spastic paraplegia and 43 with additional features). Major neurological causes of paraplegia were excluded. None had a family history of paraplegia. DNA was screened by DHPLC for mutations in the 17 coding exons of the SPG4 gene. Sequence variants were characterised by direct sequencing. A panel of 600 control chromosomes was used to rule out polymorphisms. Results: The overall rate of mutations was 12%; 19 different mutations were identified in 18 patients, 13 of which were novel. In one family, where both parents were examined and found to be normal, the mutation was transmitted by the asymptomatic mother, indicating reduced penetrance. The parents of other patients were not available for analysis but were reported to be normal. There was no evidence for de novo mutations. The mutations found in these apparently isolated patients were mostly of the missense type and tended to be associated with a less severe phenotype than previously described in patients with inherited mutations. Conclusions: : The unexpected presence of SPG4 gene mutations in patients with sporadic spastic paraplegia suggests that gene testing should be done in individuals with pure or complicated spastic paraplegia without family histories.